ANALISIS PENGARUH BUDAYA ORGANISASIONAL DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA BIDAN PADA RSUD KOTA MATARAM - Baiq Sukmawati; Lalu Suparman; Surati Surati (Master of Management, Mataram University, 2019)
This study examined the influence of organizational culture and job satisfaction on organizational commitment and performance of midwives in the Mataram City Public Hospital. Specifically the purpose of this study was to determine the significance of the influence of organizational culture, job satisfaction and organizational commitment on the performance of midwives, to know the significance of organizational culture and job satisfaction on organizational commitment, and to know the mediating role of variable organizational commitment in midwives in Mataram City Hospital. The study population was 72 midwives in charge of the RSUD Kota Mataram. This study uses structural equation model analysis (SEM analysis) with smartPLS applications. The results showed that organizational culture and organizational commitment had a significant positive effect on the performance of midwives, while job satisfaction did not significantly affect performance. Organizational culture and job satisfaction have a significant positive effect on organizational commitment. For the influence of mediation on organizational commitment, there is a full mediating role in the influence of job satisfaction on midwife performance, while the influence of organizational culture on the performance of midwives is found to have a partial mediation effect.Keywords:Organizational Culture, Job Satisfaction, Organizational Commitment, Midwife Performance.